Age of migration: international population movements in the modern world - Castles, Stephen; Miller, Mark J. (London, 1998)
On the eve of the 21st century, international migration has become a major factor in economic and political change. Millions of people move as workers, settlers or refugees, affecting all regions of the world. The new cultural diversity is challenging national borders and identity. This work analyzes population movements and their consequences on a global level. This new edition has been completely revised and updated with substantially increased coverage of new migrations in Africa, Latin America and Asia.
Keywords: Migration, International